Preschoolers’ temperament and social functioning in novel and routine contexts - Vaughan, Helena Shoplik; Teglasi, Hedwig (Frontiers in Psychology, 2022)
Introduction The centrality of social competence to children’s short and long-term well-being has sparked interest in the factors that contribute to its development, including temperament, a set of biologically based dispositions. A large body of work documents two types of temperamental dispositions associated with young children’s social functioning: reactivity and regulation. There is consensus about the detrimental effects of negative reactive tendencies, called negative affective reactivity (NA), and about the beneficial effects of regulatory tendencies, called effortful control (EC), on social functioning. Another reactive component of temperament, Extraversion/Surgency (E/S) is less consistent in its relation with social functioning. Although NA is exacerbated by lack of familiarity, its contribution to social functioning in novel and routine contexts has not been systematically addressed. Methods To test this study’s hypotheses, we devised a structured interview of adaptive responsiveness in context (ARC) which was completed by parents of preschoolers along with a comprehensive temperament questionnaire. Additionally, children completed an individually administered task measuring emotion-situation knowledge (N = 92) and their teachers completed a standard social competence questionnaire. Results and Discussion A path analysis that controlled for variance shared across contexts and temperamental traits showed that NA was the only unique predictor of social functioning in the Novel context, that EC was the only unique predictor of social functioning in the Routine context and that E/S was not a unique predictor of social functioning in either context. Bivariate analyses, conducted without controlling for context overlap, showed all reactive emotional traits (subsumed within NA and E/S) to correlate exclusively with ARC in the Novel contexts. However, regulatory traits showed a mixed pattern. Inhibitory Control correlated with ARC in both contexts but more highly in the Routine context, and Perceptual Sensitivity correlated with ARC in the Novel context.